FRI0123 BIOLOGICAL THERAPIES SURVIVAL IN RHEUMATOID ARTHRITIS PATIENTSIN CLINICAL PRACTICE: RESULTS FROM THE METEOR REGISTRY. (June 2019) - Torrente-Segarra, Vicenç; Huizinga, Thomas; Solomon-Escoto, Karen; Da Silva, José Antonio P.; Veale, Douglas; Emadi, Samar Al; Bergstra, Sytske Anne
Abstract : Background: Several biologic disease modifying anti-rheumatic drugs (bDMARDs) are currently available, but comparisons among these different drugs in clinical trials are rare and follow-up duration in trials is often limited. A comparison of these bDMARDs in daily practice can provide clinically relevant knowledge on treatment survival of all currently available bDMARDs. Objectives: To assess the survival of each and every one of the biological therapies available in patients with rheumatoid arthritis (RA). Methods: The METEOR registry is a multinational project that includes data on> 40, 000 patients with RA from its diagnosis and prospectively, with proven reliability, in clinical practice. Inclusion criteria: patients> 18 years in biological treatment (bDMARD). Variables under study: disease onset date, bDMARD initiation and discontinuation date, bDMARD type (infliximab, certolizumab, adalimumab, golimumab, etanercept, rituximab, tocilizumab and abatacept), concomitant treatment, line of treatment. Clinical variables: TJC, SJC, ESR, CRP, BMI, patient's VAS, and RF and ACPA levels; smoking status. Cox regression analysis that was adjusted for several potential confounders. Results: From the 47, 263 patients registered in the total METEOR database, 11, 132 were eligible for inclusion of the current study. Of these, 9, 516 had sufficient data available and were included in the analyses. Included patients (n=9, 516) less often smoked than non-included patients (n=1, 616), but other baseline characteristics were very similar between groups (data not shonw). Baseline features of all patients were similar. Median time on bDMARD as 1st line treatment for each drug is shown in Table 1, infliximab showed the longest median time on treatment. Using infliximab as 'reference' treatment, Table 2 shows abatacept, certolizumab, rituximab and tocilizumab showed higher hazard risk to finish the treatment prematurely, while adalimumab, golimumab or etanercept had similar results than infliximab. Conclusion: after adjusting by several confounders, analysed data showed that most anti-TNF (infliximab, adalimumab, etanercept and golimumab) had a similar hazard to stop treatment in clinical practice. Other than anti-TNF bDMARD showed higher hazard to switch treatment than infliximab. Disclosure of Interests: Vicenç Torrente-Segarra Speakers bureau: Roche, GSK, UCB, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Karen Solomon-Escoto: None declared, José Antonio P. da Silva: None declared, Douglas Veale: None declared, Samar Al Emadi: None declared, Sytske Anne Bergstra Grant/research support from: Bristol-Myers Squibb provided funding for the completion of this study and the development of the abstract.